The effect of a combination of short-chain fatty acids on plasma fibrinogen concentrations in Westernised black men - De Wet, Martie (University of the Free State, 1999)
The incidence of the western diseases, atherosclerosis, CHD and stroke is progressively rising in black populations worldwide and in South Africa. Stroke is an important cause of death in black populations in South Africa and may increases even further if risk factor (coronary and some haemostatic risk factors) prevalence is altered by change in lifestyle and diet, westernisation and migration to an urban environment. Raised fibrinogen levels which are more prevalent in westernised black men than white men, are accepted as an important risk factor for stroke and CHD. It is believed that the possible protective effects of diet against the development of atherosclerosis and thrombosis could be mediated, in part, through haemostasis. A prudent low-fat, high-fibre diet may favourably influence haemostasis. More specifically, oat bran (soluble fibre) has been shown to have beneficial effects on some coronary risk factors and haemostasis. The physiological effects of dietary fibre are strongly related to SCFAs, which are produced by colonic fibre fermentation. According to available literature, SCFAs could possibly have a beneficial effect on lipid profiles and haemostatic risk factors. Little information is, however, available on the effect of a specific combination of SCFAs on fibrinogen levels and other haemostatic factors in human subjects. The main objective of the study was to examine the effect of a combination of SCFAs, resembling oat bran (acetate:propionate:butyrate – 65:19:16) on plasma fibrinogen levels, some haemostatic risk factors and other related risk factors for CHD and stroke in westernised black men. The study was a randomised, placebo-controlled, double-blind clinical trial. 22 subjects falling within a pre-determined set of inclusion criteria, and with higher normal fibrinogen levels were randomly selected into an experimental group (n = 11) and placebo group (n = 10). Supplementation of 12 capsules daily was sustained for five weeks. Total plasma fibrinogen, fibrin monomer concentration, fibrin network properties, factor VII and factor VIII activity, serum lipids, glucose concentrations, some metabolic indicators and fasting acetate concentrations were measured at baseline and at the end of supplementation, in all subjects. The usual dietary intake of the subjects was obtained using a food frequency questionnaire and a 24-hour recall. According to the baseline results, the subject group was homogeneous with an apparently healthy clinical and physical appearance. Although both subject groups had a favourable coronary and haemostatic risk profile, total cholesterol levels as well as factor VII and factor VIII activity were in the higher normal ranges. Furthermore, the 24-hour recall indicated a tendency towards the adoption of an atherogenic Westernised diet. Although SCFA supplementation had no effect on the fibrinogen concentrations, a significant decrease was observed in the fibrin monomer concentrations, network fibrin content, factor VII and factor VIII activity. A significant increase was observed in the compaction of the fibrin networks, as well as a tendency for the mass to length ratio of the fibrin fibres to increase. Furthermore, a statistically significant although not clinically significant increase was indicated in HDL cholesterol concentrations after SCFA supplementation. It was evident from these findings that SCFA supplementation may have a direct effect on haemostasis, especially the fibrin network characteristics, factor VII and factor VIII activities, as well as fibrin monomer concentration. This observation suggests that SCFA supplementation may have a strong protective effect against atherosclerosis and thrombosis. In conclusion, the hypothesis that soluble dietary fibre will influence fibrinogen concentrations and other haemostatic risk factors through production of SCFAs, was proven to be partially true. It was clear that, although fibrinogen concentration was not influenced by SCFA supplementation, beneficial effects on the fibrin network architecture and the positive cascade effect on haemostasis may be a direct effect of SCFAs supplementation. The study further indicated that the known protective effects of dietary fibre on CHD could partially be mediated through effects of SCFAs on fibrin networks. It is recommended that the role of fibrin networks as a risk factor for CHD and the effect of diet on haemostasis should be further investigated.

Die voorkoms van die westerse siektes arteriosklerose, koronêre hartsiektes (KHS) en beroerte is besig om vinnig wêreldwyd en in Suid-Afrika toe te neem. Serebrovaskulêre siektes (beroerte) is ‘n belangrike oorsaak van sterftes in swart populasiess in Suid-Afrika. KHS en beroerte neem selfs verder toe wanneer die risikofaktore verhoog as gevolg van verwestering wat ‘n verandering in leefstyl en dieet teweeg bring. Verhoogde fibrinogeenvlakke, wat meer onder verwesterde swarte as blanke mans voorkom, word as ‘n belangrike onafhanklike risikofaktor vir beroerte beskou. Die dieet speel verder ook ‘n belangrike rol in die ontwikkeling van arteriosklerose en trombose en word moontlik gedeeltelik deur hemeostase gemedieer. Die omsigtige lae-vet, hoë-vesel dieet kan moontlik hemeostase gunstig beïnvloed. Hawersemels (oplosbare vesel) is meer spesifiek aangedui as ‘n belangrike dieetfaktor in sommige voordelige effekte van dieet op koronêre risikofaktore en hemeostase. Die metaboliese effek van dieetvesel word geassossieer met kortketting vetsure (KKV) wat in die kolon gevorm word as gevolg van fermentasie. Volgens beskikbare literatuur kan KKV moontlik ‘n voordelige effek op die koronêre en hemeostatiese risikofaktore hê. Min bewyse bestaan egter oor die effek van ‘n kombinasie van KKV op fibrinogeenkonsentrasies en ander hemeostatiese risikofaktore. Die hoofdoelwit van die studie was om die effek van ‘n kombinasie van KKV wat die fermentasieprodukte van hawersemels verteenwoordig (asetaat:propionaat:butiraat) op plasmafibrinogeenkonsentrasies en verwante risikofaktore vir KHS en beroerte in verwesterde swart mans te bepaal. Die studie was ‘n ewekansige, dubbelblinde kliniese proef. 22 proefpersone, geselekteer volgens spesifieke insluitingskriteria en hoog normale fibrinogeenvlakke, is in die studie ingesluit. Die proefpersone is ewekansig in ‘n eksperimentele groep (n=11) en ‘n kontrole groep (n = 10) verdeel. Supplementasie van 12 kapsules daagliks het vir vyf weke plaasgevind. Plasmafibrinogeenkonsentrasies, fibrienmonomeerkonsentrasies, fibriennetwerkeienskappe, faktor VII en faktor VIII aktiwiteit, serumlipiede, vastende glukose vlakke, volbloedtelling, en vastende asetaatkonsentrasies is aan die begin en die einde van die studie gemeet. Die respondente se gebruiklike voedselinname is met ‘n 24-uur herroep en voedselfrekwensie vraelys bepaal. Volgens die basislyn resultate was die steekproef ‘n kliniese en fisiologiese gesonde homogene groep. Beide groepe was normolipidemies met ‘n neigings tot hoog normale totale cholesterolvlakke, faktor VII en faktor VIII aktiwiteit. Volgens die 24- uur herroep metode het die respondente ook ‘n neiging tot die aankweek van westerse eetpatrone getoon. KKV supplementasie het geen effek op fibrinogeenkonsentrasies gehad nie, maar het die fibrienmonomeerkonsentrasies en die fibrien netwerk inhoud, faktor VII en faktor VIII betekenisvol verlaag. Verder is ‘n betekenisvolle verhoging in die kompaksies van die fibriennetwerke gevind asook ‘n neiging tot verhoging in die massa/lengte verhouding van die fibrienvesels. Hoewel, KKV supplementasie die HDL cholesterolkonsentrasiess statisties betekenisvol verander het na vyf weke, wass die effek nie klinies betekenisvol nie. Die bevindings van die studie dui aan dat KKV supplementasie moontlik ‘n direkte effek op hemeostase kan hê, spesifiek ten opsigte van die fibriennetwerkstrukture, faktor VII en faktor VIII asook fibrienmonomeerkonsentrasies. Hierdie bevindings dui moontlik aan dat KKV ssupplementasie ‘n sterk beskermende eienskap teen arteriosklerose en trombose teweeg kan bring. Die gevolgtrekking kan gemaak word dat die voordelige effek van oplosbare vesel moontlik bemiddel word deur die produksie van KKV. Dit was duidelik dat, alhoewel die fibrinogeenkonsentrasies na supplementasie onveranderd gebly het, die KKV wel die fibriennetwerkstrukture positief verander het om minder aterogenies te wees. Die studie dui dus ook aan dat die beskermende effek van dieetvesel op KHS moontlik deur die effek van KKV op die fibriennetwerke bemiddel word. Hieruit volg die aanbeveling dat die rol van fibriennetwerke as risikofaktor vir hartsiektes, asook die effek van die dieet op hierdie netwerke verder bestudeer moet word.
Dissertation (M.Sc. (Dietitics))--University of the Free State, 1999
Keywords: Blood coagulation factors; Men, Black -- Health and hygiene; Fibrinogen; Factor VIII; Factor VII; Fibrin network architecture; SCFAs; Dietary fibre; Westernisation